Penerapan Manajemen Strategik Dalam Penyusunan Perencanaan Bisnis Oleh Manajemen PT. Cigede Griya Permai Suatu Model Strategik - , Jimmy Budi Hariyanto, Prof. Mudrajat Kuncoro, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Application of the business plan principle is an effort to realize the continuity of the company to achieve sustainability objectives better than the previous year. Sustainability measurement of financial capacity, customer satisfaction, production processes, learning and growth are the basis for setting improvement targets will be achieved. A business plan is an attempt to transform vision, mission and strategy into objectives and measures in a balanced set of perspectives. Scorecards are used in the four perspectives, consist of various size companies the desired results and also the various processes that will encourage the achievement of the desired future outcomes that are essentially include: financial perspective, customer perspective, internal business process perspective, and learning & growth perspective. To analyze the performance of PT. Cigede Griya Permai, to determine the application of balanced scorecard strategy in the construction of PT. Cigede Griya Permai business plan and to discover what constraints are experienced by PT Cigede Griya Permai in the process of developing and implementing the business plan, through the optimization of four perspective balance scorecard. Performance PT. Cigede Griya Permai at this point are require to be improved and the reviewed based on the principles of balanced scorecard. The future application need to be implemented, by unified vision, mission and strategy among all lines of management. To overcome the shortcomings that occurred, need to continue with improvements holistically, with the seat all the relevant parties to implement the performance tailored to the business plan which refers to the balance scorecard.